DNA Methylation Sustains “Inflamed” Memory of Peripheral Immune Cells Aggravating Kidney Inflammatory Response in Chronic Kidney Disease - Chen, Xiao-Jun; Zhang, Hong; Yang, Fei; Liu, Yu; Chen, Guochun (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD), irrespective of its etiology, is generally accompanied with chronic kidney inflammation that is pathologically featured by accumulation of infiltrated immune cells in the tubulointerstitial compartment. Although recruited immune cells might facilitate tissue regeneration in acute kidney injury (AKI), chronic infiltration of peripheral immune cells conversely contributes to kidney maladaptive repair and CKD progression. The underlying mechanism, of which recruited immune cells act differently in diseased kidney, remains largely unknown. DNA methylation plays a vital part in regulating immunocytes biology by induction of permissive or negative genes expression. We have recently revealed that persistent hyperglycemia in type 2 diabetes aberrantly alters DNA methylation profile of circulating immune cells, which migrate into diabetic kidneys and participate in chronic inflammatory response. Based on our and the others' findings, we propose here a model of epigenetic regulation in CKD pathogenesis: chronic pathogenic conditions initiate aberrant DNA methylation in peripheral immune cells; this "inflamed" memory sustains a pro-inflammatory phenotype of the recruited immune cells in diseased kidneys, consequentially resulting in uncontrolled kidney inflammation and CKD progression. This review will outline the current knowledge about the role of DNA methylation in CKD development with a particular focus on peripheral immune cells.